Expanding the Scope of the Cleavable N-(Methoxy)oxazolidine Linker for the Synthesis of Oligonucleotide Conjugates - Aho Aapo; Äärelä Antti; Korhonen Heidi; Virta Pasi (MDPI, 2022)
Oligonucleotides modified by a 2 '-deoxy-2 '-(N-methoxyamino) ribonucleotide react readily with aldehydes in slightly acidic conditions to yield the corresponding N-(methoxy)oxazolidine-linked oligonucleotide-conjugates. The reaction is reversible and dynamic in slightly acidic conditions, while the products are virtually stable above pH 7, where the reaction is in a ''switched off-state''. Small molecular examinations have demonstrated that aldehyde constituents affect the cleavage rate of the N-(methoxy)oxazolidine-linkage. This can be utilized to adjust the stability of this pH-responsive cleavable linker for drug delivery applications. In the present study, Fmoc-beta-Ala-H was immobilized to a serine-modified ChemMatrix resin and used for the automated assembly of two peptidealdehydes and one aldehyde-modified peptide nucleic acid (PNA). In addition, a triantennary N-acetyl-d-galactosamine-cluster with a beta-Ala-H unit has been synthesized. These aldehydes were conjugated via N-(methoxy)oxazolidine-linkage to therapeutically relevant oligonucleotide phosphorothioates and one DNA-aptamer in 19-47% isolated yields. The cleavage rates of the conjugates were studied in slightly acidic conditions. In addition to the diverse set of conjugates synthesized, these experiments and a comparison to published data demonstrate that the simple conversion of Gly-H to beta-Ala-H residue resulted in a faster cleavage of the N-(methoxy)oxazolidine-linker at pH 5, being comparable (T-0.5 ca 7 h) to hydrazone-based structures.